Some Fixed Point Theorems in K-Metric Type Spaces: A. Taheri, Ali Farajzadeh, Suthep Suantai - Team, Support (Thai Journal of Mathematics, 2022)
In this paper, K-metric type spaces, generalized KKM mappings, KKM property and fixed point property are introduced. Moreover a relationship between KKM property and fixed point property is established and finally some fixed point theorems in K-metric type spaces are presented.